Ergonomic Risk Assessment of Static Postures and Repetitive Tasks using Rapid Entire Body Assessment and Strain Idex - Anh Le (Industrial Engineering Department, Faculty of Science and Engineering, UIN Sunan Kalijaga Yogyakarta, 2021)
This study aims to assess the risk levels of work-related musculoskeletal disorders (WMSDs) of Vietnamese female workers performing repetitive tasks and static postures. The workers perform the repetitive tasks which are printed circuit board assembly and printing on housing in a factory in Ho Chi Minh City, Vietnam. The risk assessment tools are used consisting of Rapid Entire Body Assessment and Strain Index. The result shows that the risk levels of WMSDs of workers are from medium to high levels. Therefore, ergonomic measures are needed to reduce the risk levels and improve the working conditions. The suggestions of ergonomic interventions are ergonomic workstation redesign considering anthropometric data of Vietnamese female workers, appropriate work methods and training for workers.